2017
DOI: 10.1177/0269881117691453
|View full text |Cite
|
Sign up to set email alerts
|

The association of psychedelic use and opioid use disorders among illicit users in the United States

Abstract: Experience with psychedelic drugs is associated with decreased risk of opioid abuse and dependence. Conversely, other illicit drug use history is largely associated with increased risk of opioid abuse and dependence. These findings suggest that psychedelics are associated with positive psychological characteristics and are consistent with prior reports suggesting efficacy in treatment of substance use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 49 publications
(49 reference statements)
2
31
0
Order By: Relevance
“…Building on these findings, Argento et al (2017) found that psychedelic drug use, broadly defined (i.e., not restricted only to 5HT2A agonists but also including MDMA) prospectively predicted a reduced likelihood of suicide ideation or attempts among 290 marginalized Canadian women (aHR = 0.40). Moreover, consistent with pilot studies of psilocybin-assisted psychotherapy for drug dependence (Bogenschutz et al, 2015; Johnson et al, 2014), Pisano et al found that lifetime classic psychedelic use was associated with a reduced risk of past year opioid dependence (weighted risk ratio = 0.73) and past year opioid abuse (weighted risk ratio = 0.60) among over 44,000 illicit opioid users who completed the NSDUH in years 2008 through 2013 (Pisano et al, 2017). Finally, a growing literature suggests protective effects for individuals in the criminal justice system, who suffer from numerous comorbid psychopathologies including depression, anxiety, and drug dependence that exacerbate criminal behavior.…”
Section: Evaluation Of the Abuse Potential Of Psilocybin According Tomentioning
confidence: 78%
“…Building on these findings, Argento et al (2017) found that psychedelic drug use, broadly defined (i.e., not restricted only to 5HT2A agonists but also including MDMA) prospectively predicted a reduced likelihood of suicide ideation or attempts among 290 marginalized Canadian women (aHR = 0.40). Moreover, consistent with pilot studies of psilocybin-assisted psychotherapy for drug dependence (Bogenschutz et al, 2015; Johnson et al, 2014), Pisano et al found that lifetime classic psychedelic use was associated with a reduced risk of past year opioid dependence (weighted risk ratio = 0.73) and past year opioid abuse (weighted risk ratio = 0.60) among over 44,000 illicit opioid users who completed the NSDUH in years 2008 through 2013 (Pisano et al, 2017). Finally, a growing literature suggests protective effects for individuals in the criminal justice system, who suffer from numerous comorbid psychopathologies including depression, anxiety, and drug dependence that exacerbate criminal behavior.…”
Section: Evaluation Of the Abuse Potential Of Psilocybin According Tomentioning
confidence: 78%
“…Participants in the present research were adult (≥18 years old) respondents of the NSDUH pooled across years 2002 through 2014 (the maximum number of survey years providing the same variables for analysis; unweighted Ns for all analyses > 480,000). Similar approaches have been employed by five prior investigations evaluating population-level associations of classic psychedelic use with indices of mental health (Hendricks et al, 2015a, b;Johansen and Krebs, 2015;Krebs and Johansen, 2013;Pisano et al, 2017). Detailed information on the NSDUH can be found elsewhere (https:// nsduhweb.rti.org/respweb/homepage.cfm).…”
Section: Methodsmentioning
confidence: 98%
“…Biologically verified continuous abstinence was significantly greater in the LSD than control conditions at 6 month (32% vs. 8%) and 12 month (25% vs 5%) follow-ups (46). Epidemiological data from the 2008-2013 National Survey on Drug Use and Health showed lifetime serotonin 2A agonist psychedelic use was associated with 27% reduced risk of past year opioid dependence and 40% reduced risk of past year opioid abuse when controlling for relevant covariates (43). Preliminary observational data have shown significant reductions in cocaine use in a small sample (n = 6) after participation in a ceremonial ayahuasca retreat geared toward addressing substance misuse (47).…”
Section: Introductionmentioning
confidence: 92%
“…Use of serotonin 2A (5-HT2A) agonist psychedelics such as lysergic acid diethylamide (LSD), psilocybin-containing mushrooms (hereafter referred to as psilocybin), peyote, and the dimethyltryptamine (DMT) containing admixture ayahuasca in both naturalistic and clinical settings have been implicated in decreased substance misuse (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). The strongest evidence is for LSD in the treatment of alcoholism, with six randomized studies showing an aggregated statistically significant effect for LSD improving outcomes in meta-analysis (49).…”
Section: Introductionmentioning
confidence: 99%